(untitled) (Nonconventional Technologies Review, 2016)
This paper presents the results of experimental research on the behavior of tool- electrodes made of copper, brass, aluminum and graphite by applying pulsed electrical discharges. The electrodes applied to the formation of the surface layers are made of conductive materials subjected to different energetic modes during the experimental investigations. The authors studied the effects that appear between the base electrodes (anode and cathode) varying the polarity and charging voltage of the capacitor while the other regimes remain constant (gap, DEI frequency, capacity and time).